(untitled) (The Review of Diabetic Studies, 2025)
Micro, Small, and Medium Enterprises (MSMEs) form an intricate part of Indian Economy. Their contribution spans from employment generation, revenue building, entrepreneurship to innovation. Yet the sector is prone to face multiple risks and financial instability. Insurance would be a right risk management device which can help the MSMEs to immune themselves. However, the studies suggest that the MSMEs remain largely underinsured, particularly in the micro segment where affordability, product suitability, and awareness continue to be major barriers. This study investigates the relationship between business category and three perceptual factors, premium affordability, customized affordability, and perceived match of benefit and their influence on insurance adoption among 164 MSMEs in the Peenya Industrial Area, Bengaluru. Correlation analysis revealed weak associations between business category and perceptions of affordability, while regression analysis indicated that none of the three perceptual variables were statistically significant predictors of insurance adoption, despite showing positive directional coefficients. These findings suggest that affordability and suitability, though important, do not independently drive adoption. Instead, factors such as awareness, trust in insurers, service quality, and government incentives also play their roles in influencing decision-making. The study concludes that improving insurance penetration among MSMEs requires a holistic approach that goes beyond low premiums, emphasizing targeted awareness campaigns, transparent claim processes, flexible payment structures, bundled products, and government-backed support mechanisms would help increase insurance inclusion among MSMEs.